Changes of macular vessel density and thickness in gas and silicone oil tamponades after vitrectomy for macula-on rhegmatogenous retinal detachment - Yang Liu (BMC, 2021)
Abstract Purpose To investigate the macular vessel density and thickness in macular-on rhegmatogenous retinal detachment (RRD) after vitrectomy with gas and silicone oil (SO) tamponade. Methods Patients with macular-on RRD eyes, treated with a single successful vitrectomy with gas or SO tamponade and a minimum 30 months follow-up, were reviewed. Best-corrected visual acuity (BCVA), macular vessel density and retinal thickness by using optical coherence tomography angiography, were compared to the contralateral eyes. Results Sixteen eyes with gas tamponade and 17 eyes with SO tamponade were included in the study. LogMAR best-corrected visual acuity (BCVA) slightly improved from 0.25 ± 0.18 (Snellen 20/36) to 0.17 ± 0.23 (Snellen 20/30) in eyes with gas tamponade, and decreased from 0.30 ± 0.22 (Snellen 20/40) to 0.49 ± 0.28 (Snellen 20/62) in eyes with SO tamponade. The parafoveal vessel densities in superficial vascular complex (SVC) and the corresponding inner retinal thickness (IRT) were similar between the affected eyes and the contralateral eyes in gas tamponade group (P = 0.578, P = 0.943), while significantly reduced in the affected eyes, compared to the contralateral eyes in SO tamponade group (P < 0.001, P < 0.001). Conclusion Eyes in SO tamponade group had worse BCVA, lower SVC vessel densities and thinner corresponding IRT after vitrectomy for macular-on RRD, than those in gas tamponade group.